Pengaruh Independensi, Pengalaman Kerja, Tingkat Pendidikan dan Pelatihan Kerja Terhadap Efektivitas Struktur Pengendalian Intern LPD - Wulandari, Luh Ratna; Latrini, Made Yenni (E-Jurnal Akuntansi, 2018)
National development is a series of interconnected development including society, nation, and state. One of the things that can support the national development is the economy that must be started from the most basic level, namely the village level. One of the forms of development in the economic field in the village is to establish village financial institutions that are ready for capital housing settlements. This study aims to determine the influence of independence, work experience, level of education and employee training on the function of internal control structure of village credit institutions. The method of determining the sample used in this study is purposive sampling technique with a sample of 92 people. Data analysis technique used is multiple linear regression analysis. The results of this study indicate a significant independence on the effectiveness of village credit institutions. Significant significant work experience on the effectiveness of village credit institutions. The level of education and job training significantly significant to the effectiveness of village credit institutions. In relation to the results and discussion in this study, it is expected that each LPD should pay more attention to work experience, education and job training level when receiving an employee and also to improve and maintain the independence attitude of the employee while performing the task in order to create an effective internal control Keywords: independence, work experience, level of education and job training, effectiveness of internal control structure, Village Credit Institution.